PENGARUH PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN EFIKASI DIRI PADA SISWA SMK - Galas Esha Prananda (ADIBA : JOURNAL OF EDUCATION, 2024)
Based on the results of the Program for International Student Assessment (PISA) study, it shows that Indonesian students' self-confidence in their abilities or self-efficacy is below average. Given these problems, a learning model is needed that can influence students' self-efficacy. This research aims to analyze the influence of Project-Based Learning (PjBL) in increasing the self-efficacy of Vocational High School (SMK) students. PjBL learning has become the main focus in efforts to increase self-efficacy in vocational school students. This article conducts a critical study of the influence of PjBL in increasing vocational school students' self-efficacy. By integrating theories of learning and self-efficacy, we explore empirical evidence supporting the role of PjBL in strengthening students' beliefs in their abilities to achieve academic and professional goals. In addition, we analyze the factors and processes that influence PjBL in increasing self-efficacy in vocational school students and provide recommendations to increase its effectiveness. Through this research, we hope to provide valuable insights for educators, policy makers, and educational practitioners, as well as provide a foundation for further research in this domain.